(untitled) (Acta Horti Botanici Bucurestiensis, 2024)
This study presents an assessment of the Artemisia collection at the BUC Herbarium of the University of Bucharest, which holds 324 specimens spanning 19 taxa collected over more than a century. The aim was to document and organize the collection, ensuring accurate taxonomic identification, correcting nomenclatural inconsistencies, and creating a digital database for improved accessibility. This work draws on the contributions of numerous historic collectors, enriching the collection’s significance as a botanical and ecological resource. Through continued curation and digitization, the BUC Herbarium contributes essential data for taxonomic, ecological, and conservation research.